Anti-influenza therapy: the emerging challenge of resistance. Issue 6 (November 2009) - Ison, Michael G
Influenza is a common cause of respiratory infections, with an annual peak incidence in the late fall, winter and early spring. It is associated with significant morbidity and mortality, particularly in those at the extremes of life and with underlying medical conditions, as well as self-limited illness with reduced productivity in otherwise healthy individuals. Two classes of antiviral medications, M2 inhibitors and neuraminidase inhibitors, are widely available. Use of these agents is associated with reduction in severity and duration of illness, and may be associated with reduced risk of death in certain patient populations. They also are effective in preventing influenza, in addition to or instead of immunization. Unfortunately, widespread resistance to one of the two classes of drugs is now common among most circulating strains of influenza.